2017
DOI: 10.7759/cureus.988
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Severity Classification of Acute Exacerbation of Chronic Obstructive Pulmonary Disease and Clinical Outcomes in Hospitalized Patients

Abstract: BackgroundLimited data are available regarding the impact of the potential validation of the Canadian Thoracic Society (CTS) guidelines recommendations in classifying patients with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD) in simple and complex. The aim of the present study was to assess the CTS recommendations regarding risk stratification on clinical outcomes among patients hospitalized with an AECOPD.MethodsWe developed a retrospective cohort study of patients admitted to one t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…There were three studies 127,190,238 with sample sizes of less than 20, and another three studies 80,134,194 with sample sizes of 20-40 patients. Moreover, there were three studies 98,119,210 with no females included in the sample, and another 52 studies [20][21][22][23]29,32,38,42,51,53,[68][69][70]72,74,88,90,91,94,116,139,[143][144][145][146][147][148][149]155,159,[161][162][163]173,177,181,182,190,192,193,…”
mentioning
confidence: 99%
“…There were three studies 127,190,238 with sample sizes of less than 20, and another three studies 80,134,194 with sample sizes of 20-40 patients. Moreover, there were three studies 98,119,210 with no females included in the sample, and another 52 studies [20][21][22][23]29,32,38,42,51,53,[68][69][70]72,74,88,90,91,94,116,139,[143][144][145][146][147][148][149]155,159,[161][162][163]173,177,181,182,190,192,193,…”
mentioning
confidence: 99%
“…≥4 exacerbations in the last year, 4. presence of serious comorbidities (ischemic heart disease, ...), 5. use of home oxygen, 6. chronic oral steroid use, 7. older age and 8. failure of an exacerbation to respond to initial medical management. If a least one risk factor was present at the moment of admission, COPD exacerbation was considered as a complex acute exacerbation with need for hospitalisation (16,19).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of ICU admission rates ranges from 2 to 19% for all the AECOPD cases requiring hospitalization [13][14][15][16]. Many studies have shown some limitations in collecting these epidemiologic data: the main issues are the heterogeneity of COPD study populations, the different selection criteria for ICU admissions, and the ICU stay durations, which vary according to the healthcare system variabilities among different countries.…”
Section: Aecopd In Icu Setting: Epidemiologymentioning
confidence: 99%